Effect of sugammadex on rocuronium induced changes in pancreatic mast cells. (August 2015) - Kalkan, Yıldıray; Tumkaya, Levent; Bostan, Habib; Tomak, Yakup; Altuner, Durdu; Yilmaz, Adnan; Erdivanli, Başar; Bedir, Recep; Yalcin, Alper; Turan, Alparslan
Mast cells play a vital role in hypersensitivity reactions. Rocuronium is known to cause mast cell mobilization, hypersensitivity, and pancreatitis. The aim of this study was to investigate the effects of sugammadex on pancreatic changes due to rocuronium. A total of 42 Sprague-Dawley male rats were divided into six equal groups to receive either rocuronium 1 mg/kg intravenously (i.v., R group), rocuronium 1 mg/kg + sugammadex 16 mg/kg i.v. (RS16 group), rocuronium 1 mg/kg + sugammadex 96 mg/kg i.v. (RS96 group), sugammadex 16 mg/kg (S16), sugammadex 96 mg/kg i.v. (S96 group), or 0.9% sodium chloride (control group). Sugammadex was administered 5s later following rocuronium. In R group, mast count was higher, and the distribution rate of granules and nuclear changes were different compared with other groups. Distribution rate of granules in groups S16 and S96 were similar to the control group and lower compared with other groups. The amount of mast cells and granule density in groups RS16 and RS96 was lower compared with R group. The amount of mast cells in groups RS16 and RS96 was significantly lower compared with other treatment groups. These results suggest that sugammadex may have an inhibitory effect on mobilization and morphological changes in pancreatic mast cells induced by administration of rocuronium and sugammadex in rats.